At MAGIC, Innovation Sought To Blunt Rising Costs - Palmieri, Jean E; Brown, Rachel (WWD)
LAS VEGAS — The squeeze is on. Facing a perfect storm of rising raw material prices, increased production costs and slow deliveries, retailers are getting slammed with a rise in wholesale prices of 10 to 15 percent for spring.